English Reading Materials in Vocational High School: A Need Analysis - Syaifuddin Syaifuddin; Natalina Asi; Elanneri Karani (Jurnal Bahasa dan Sastra, 2022)
This research elucidates the students’ needs through need analysis in the context of vocational high school. Need analysis had been considered as the crucial factor and an integral part of establishing an ESP course as it is only through the process of need analysis researchers, course designers, and material developers are able to determine and refine the content for an ESP course that meets the learners’ need. This research was conducted online in Kapuas Regency. Therefore, the participants of the study are students of Agriculture program in some SMK in Kapuas Regency. They are SMKN 3 Kuala Kapuas, SMKN 4 Kuala Kapuas, SMKN 1 Bataguh, SMKN 1 Kapuas Murung, SMKN 1 Mantangai, SMKN 2 Mantangai, SMKS Bethel Kaladan, SMKN 1 Timpah. The research was descriptive quantitative research The writer used random sampling method. The data were gathered from research participants via questionnaire in order to analyze the students’ need in learning English especially for reading. The questionnaire was based on the Hutchinson & Waters' model of Needs Analysis.  The results of the research indicated that English language teaching should be taught in specific ways and materials. The literacy rate of students in vocational high schools in Kapuas regency was still quite low. The students also rarely to improve their receptive skills rather than productive skills. furthermore, the grammar was learnt inductively. Besides that, the average level of English proficiency of the students was at beginner level.  In addition, the amount of English vocabulary about agriculture was about less than 100 words and the rest of students had 100-500 words. The students also had some problems in reading.